Botswana Digital Economy Diagnostic - World Bank (Washington, DC, 2022)
Digital technologies are paving the way for economic growth and new service delivery models across Africa. On key digital indicators, Botswana fares similarly or better than regional neighbors, but is lagging behind global peers with the same income levels, illustrating the potential to enhance performance. The digital economy in Botswana rests on several relatively strong individual strategies, policies, and regulations. However, when combined, these form a somewhat fragmented framework - further challenged by oftentimes slow implementation. This digital economy for Africa (DE4A) report considers the digital economy’s five foundational pillars, as well as cross-cutting issues. The report summarizes pillar status and recommendations for addressing challenges: infrastructure; digital platforms; digital financial services (DFS); digital business; digital skills; and suggested priority areas for action.